La mesure de la productivité (Relations industrielles / Industrial Relations, 1952)
The article reviews "La mesure de la productivité," by Jean Dayre, conseiller technique du Comité national de la productivité. Series of three articles published successively in the october, november and december 1951 issues of the journal, Travail et Méthodes. Editions Science et Industrie, Paris.